The Association of Mother’s Education with the Determinants of Typhoid Fever among Children: A Cross-Sectional Study - Munwar us Salam; Chandio, Atta Muhammad; Sheikh, Abrar Ali; Parveen, Rubina; Raza, Saad; Rahimoon, Muhammad (Indus Journal of Bioscience Research, 2025)
Objective: To highlight the association of mother’s education with the determinants of typhoid fever among children. Methodology: A Cross sectional study design was used at MNCH Nawabshah, SBA. The total of 350 n patients were selected through the manual sample size formula, non-probability convenient sampling strategy was applied. Mothers of cases/ children aged between 0 to 12 years with typhoid fever having positive test (Typhoid) or Blood Culture either getting treatment or newly diagnosed cases confirmed through laboratory report and treatment or follow up were included and Non -consenting mothers or guardians has been excluded. Data related to role of the mother’s education in social determinants of typhoid fever was collected through structured questionnaire. Confidentiality of the participant’s information was ensured during data collection, analysis and interpretation. Results: A total of 350 respondents were included in this study after fulfill inclusion and exclusion criteria with mean age of children 6.79 with ± 2.924 standard deviation (Figure 1) 46% 4-7 years of age & 30% 8-12 years 24% 1-3 Years of age. The majority of patients were 57.4% Male & 42.6% Female (Figure 2) & majority were rural residence 187 (54%) and remaining 163 (46%) urban (Figure 3). Table 1 shows the level of mother’s education that among illiterate 143 (70%), primary 52 (15%), Matriculation 32 (9%), intermediate 15 (4%), and graduation 7 (2 %). In the connection result shows that wash your hands After Eating is significant associated with the level of mother’s education (p 0.013), it is also wash your hand with Soap is highly significantly associated (p 0.000). Conclusion: The hand washing practices among the children and the mothers were evaluated and the findings of the study revealed that there is dire need of initiating the interventions for promoting hand washing among mothers and children.